Shoulder Function During Overhead Lifting Tasks: Implications for Screening Athletes. Issue 5 (October 2015) - Howe, Louis P.; Blagrove, Richard C.
Abstract : ABSTRACT: OVERHEAD EXERCISES ARE COMMON PLACE IN MANY STRENGTH AND CONDITIONING PROGRAMS. AN ESSENTIAL ELEMENT OF SUPPORTING LOAD ABOVE HEAD IS THE DEMONSTRATION OF OPTIMAL JOINT KINEMATICS AT THE SHOULDER COMPLEX. THIS ARTICLE WILL CONSIDER VARIOUS DYSFUNCTIONAL MOVEMENT STRATEGIES THAT MAY PRESENT DURING OVERHEAD LIFTING EXERCISES, POTENTIALLY EXPOSING AN ATHLETE TO PATHOLOGY. A SCREENING PROCESS WILL ALSO BE DISCUSSED, PROVIDING COACHES WITH A THOUGHT-PROCESS IN WHICH THEY MAY ASSESS AN ATHLETE'S SUITABILITY FOR OVERHEAD LIFTING EXERCISES BASED ON THEIR MOVEMENT COMPETENCY.